The equations of motion of the main structure with attached multiple tuned mass dampers - Piotr Wielgos (Budownictwo i Architektura, 2012)
A mathematical model of structure with multiple tuned mass dampers (MTMD) is presented in this paper. An important difficulty, connected with these model, is building a global damping matrix of the system. The own proposals FEM elements describing additional elements attached to the main system in the form of tuned dampers have been proposed here. The benefits of the new FEM elements have been briefly discussed.